IMPLEMENTATION OF THE POLRI SUPER APP PROGRAM IN THE POLICE RECORD CERTIFICATE (SKCK) SERVICE AT THE INTELLIGENCE AND SECURITY UNIT OF TANJUNG PERAK PORT POLICE - Ibra Yuniar Kurniawan; Heru Irianto; Fierda Nurany; Tri Prasetijowati; Bagus Ananda Kurniawan (Journal of Social Politics and Governance (JSPG), 2026)
This study examines the implementation of the Super App Polri program in the Police Record Certificate (SKCK) service at the Intelligence and Security Unit of the Tanjung Perak Port Police. Using a descriptive qualitative approach through interviews, observations, and documentation, the research adopts Edward III’s policy implementation model consisting of communication, resources, disposition, and bureaucratic structure. The findings show that the program has been implemented effectively, supported by structured coordination meetings, targeted socialization efforts, adequate facilities, competent personnel, positive officer attitudes, and clear Standard Operating Procedures. However, several obstacles remain, including limited public dissemination, low digital literacy, unstable internet connectivity, and insufficient digital devices among applicants. To address these issues, the police unit conducts routine evaluations, expands socialization through various media, provides direct assistance for digitally inexperienced users, and strengthens internal coordination. These continuous improvement efforts demonstrate Polri’s commitment to advancing a digital public service system that is more accessible, transparent, and efficient.